Determinants of corporate social responsibility on companies experience - Asna, Asna; Kamaruddin, Roslina (Akademia Baru, 2017)
This study is organized the nexus between social responsibility and financial performance both theoretical examination and empirical evidence. It aims to explicate the prior view of corporate social responsibility and the contribution of stakeholder theory on corporate social responsibility approach on business activities. It may provide a portrait the importance of social responsibility in business and society. The integration between corporate social responsibility and financial performance will emerge on business operations in developed countries particularly in developing countries. Consequently, corporate social responsibility is not perceived as diminished interest shareholders parties as well as reduction business profit. So that the corporate social responsibility concept will be continually developed to answer the development of dynamic businesses.